Spatial Projects by Dvizhenie Collective and the Emergence of Installation Art in Russia - Makeeva, Svetlana O. (Actual Problems of Theory and History of Art, 2024)
The article focuses at the intersection of two underexplored fields: the history of Russian installation art and the history of Russian kinetic art. The question of what work can be called the first installation in Russia is as relevant as it is debatable. In turn, studying the work of the kinetic collective ’Dvizhenie’ (Movement), whose members were the first Soviet unofficial artists to create large spatial projects, is a challenging research task for a whole number of reasons. The present article aims to reveal what role the projects by ’Dvizhenie’ played in the formation of installation art in Russia. The article examines the conceptual and theoretical framework of Russian kinetic art, building upon the texts by the ’Dvizhenie’ ‘s leader Lev Nusberg. Further, utopian projects (Artificial Bionic-Kinetic Environment), as well as actually realized exhibition design projects by ’Dvizhenie’, are addressed — mainly, the ’Electronics-70’ exhibition. In conclusion, the legacy of the collective is compared with the Western history and theory of installation art and is placed within the general context of installation art in Russia. The article is based on unpublished materials from the Archive of the Garage Museum of Contemporary Art.